2003
DOI: 10.1152/ajpcell.00463.2002
|View full text |Cite
|
Sign up to set email alerts
|

Loss of active MEK1-ERK1/2 restores epithelial phenotype and morphogenesis in transdifferentiated MDCK cells

Abstract: Schramek, Herbert, Elisabeth Feifel, Ingrid Marschitz, Nadejda Golochtchapova, Gerhard Gstraunthaler, and Roberto Montesano. Loss of active MEK1-ERK1/2 restores epithelial phenotype and morphogenesis in transdifferentiated MDCK cells. Am J Physiol Cell Physiol 285: C652-C661, 2003; 10.1152 10. /ajpcell.00463.2002tive activation of the MAPK/ERK kinase (MEK)1-ERK2 signaling module in Madin-Darby canine kidney (MDCK)-C7 cells disrupts their ability to form cystlike structures in collagen gels and induces an inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
2
41
1
Order By: Relevance
“…Because of the simplicity of its morphogenetic process, MDCK cyst formation is an ideal model for determining the cellular events critical for epithelial morphogenesis and the molecular mechanism(s) governing it. The signaling involved in MDCK cyst formation has emerged from various studies (Mangoo-Karim et al, 1989;Orellana and Marfella-Scivittaro, 2000;O'Brien et al, 2001;Schramek et al, 2003;Yu et al, 2005). The importance of the microenvironment in cystogenesis is well documented (Lin and Bissell, 1993;Kleinman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the simplicity of its morphogenetic process, MDCK cyst formation is an ideal model for determining the cellular events critical for epithelial morphogenesis and the molecular mechanism(s) governing it. The signaling involved in MDCK cyst formation has emerged from various studies (Mangoo-Karim et al, 1989;Orellana and Marfella-Scivittaro, 2000;O'Brien et al, 2001;Schramek et al, 2003;Yu et al, 2005). The importance of the microenvironment in cystogenesis is well documented (Lin and Bissell, 1993;Kleinman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…18,41 Especially in the renal tubular system, strong evidence exists for an important function of the MEK1/2-ERK1/2 signaling module in EMT. 10,[42][43][44] Furthermore, it has been reported that OSM represents a strong stimulator of both ERK1/2 and STAT1/3 signaling in human PTC. 10 In summary, the final functional cellular outcome of differential NRP isoform expression in renal cells such as tubular epithelial cells or tubulointerstitial fibroblasts could be controlled by gradients of extracellular ligands, by coexpression of signaling receptors, such as plexins or VEGFRs, and by ligands acting through NRPs and their co-receptors.…”
Section: Differential Neuropilin Expression In Fsgs H Schramek Et Almentioning
confidence: 99%
“…Thus, the effects of K-ras mutation may be less aggressive in tissues (such as the intestinal epithelium) in which these pathways are normally activated and where the appropriate feedback loops are expressed. In this light it is of interest to note that within Madin Darby canine kidney cells loss of active ERK͞MEK signaling restores cells to an epithelial state (26).…”
Section: Expression Of K-ras V12 Accelerates Tumorigenesis and Causesmentioning
confidence: 99%